2022
DOI: 10.1093/sleep/zsac179
|View full text |Cite
|
Sign up to set email alerts
|

Comparative associations of oximetry patterns in Obstructive Sleep Apnea with incident cardiovascular disease

Abstract: Study Objectives Intermittent hypoxia is a key mechanism linking Obstructive Sleep Apnoea (OSA) to cardiovascular disease (CVD). Oximetry analysis could enhance understanding of which OSA phenotypes are associated with CVD risk. The aim of this study was to compare associations of different oximetry patterns with incident CVD in men and women with OSA. Methods Sleep Heart Health Study data were used for analysis. N=2878 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Of note, the excess in mortality was due to malignant rather than cardiovascular diseases [ 11 ]. Our results are in line with a recent study by Sutherland et al, who reported that TST90% was more strongly related to incidental cardiovascular disease than TST80% [ 27 ]. Our study extends the former one, as it also investigated individual components contributing to the cardiovascular risk.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of note, the excess in mortality was due to malignant rather than cardiovascular diseases [ 11 ]. Our results are in line with a recent study by Sutherland et al, who reported that TST90% was more strongly related to incidental cardiovascular disease than TST80% [ 27 ]. Our study extends the former one, as it also investigated individual components contributing to the cardiovascular risk.…”
Section: Discussionsupporting
confidence: 93%
“…In a large cohort of community-dwelling older men, in contrast to TST90%, TST80% > 1% was an independent risk factor for all-cause mortality [ 11 ]. On the other hand, in the Sleep Heart Health Study, TST90% but not TST80% was related to incidental cardiovascular disease [ 27 ]. The discrepancy could be due to the different burden of cardiovascular risk factors, such as blood lipids or hypertension, which were not reported in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The results of each HB calculation method were considered as three different SpO2 predictors and compared by considering the log-transformed normalised HB value. A log transformed and the resulting distribution of the HB values was more Gaussian and had been previously used by other researcher [12,20]. Normalisation was achieved by converting each set of HBs values to z-scores by subtracting the mean value and dividing by its standard deviation.…”
Section: Cox Proportional Hazard Regression Analysismentioning
confidence: 99%
“…Although these metrics are well described in text format, there are still particularities in their implementations ( 10 ). Thus, this is also an opportunity to consider reproducibility and the recent and significant movement by the NIH toward promoting rigorous and transparent research ( 11 ).…”
mentioning
confidence: 99%